Health Literacy Levels and Affecting Factors of Patients Who Applied to a University Hospital Polyclinic - Yakar, Burkay; Gömleksiz, Mehtap; Pirinççi, Edibe (Eurasian Society of Family Medicine, 2019)
Aim: It is known that increasing health literacy can increase people's quality of life, enable them to benefit from health services more effectively and contribute to reducing health care costs. Inadequate health literacy has been reported to lead to insufficient health information, high risk of ill health, low level of understanding of treatment methods and increase in health care costs. Today, increasing number of chronic diseases, increasing the elderly population and increasing the budget allocated to health services have also increased the importance of health literacy levels. In this context, it is aimed to investigate health literacy levels and factors affecting our country. Methods: Our cross-sectional study was conducted in voluntary patients who applied to the family medicine outpatient clinic of a university. In our study, sociodemographic questionnaire form and Turkish Health Literacy Scale were used for data collection. Chi-square test was used for statistical analysis and p <0.05 was accepted as statistically significant. Results: 225 volunteers were included in our study. 62,1% of them were women. The mean score of the health literacy scale was 25.5±10.2. 50.6% of the participants were inadequate, and 25.1% of them had problematic health literacy level. The level of health literacy was found to be significantly lower in women, who had low education level, who were married and had children and who had vision problems. Conclusion: The data obtained from our study showed that our health literacy levels are low. We need to develop policies that increase our levels of health literacy to protect both public health and reduce the financial burden on health care by examining risk factors. © 2019, Eurasian Society of Family Medicine. All rights reserved.
Bir Üniversite Hastanesi Polikliniğine Başvuran Hastaların Sağlık Okuryazarlığı Düzeyleri ve Etkileyen Faktörler
Keywords: drug utilization; evaluation; health literacy; health literacy level; Turkish Health Literacy Scale